(3bWY GdhJjf ef GdeGQb aj GdOjfs - (3CHh YHO Gddg eMeO Hf YHO GdSdGe GdOQYj GdfGUQj,J (B1239 (3g` s
(3ChdgG (B:s
(3MeO Gddg JYGdi ebOe Ydi cd CeQ hHYO aEfc CjOc Gddg HJhajbg SCdJ gd jLhR ddCfS HjY ChdGOg s
(3BNQgG (B:s
(3NJe Gddg dfG HGdEjeGf hGdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi dhdG Gf gOGfG Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GfJgi GdeDda ef JGdjag SfI (B1207 (3g`s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCSJGP YHO Gddg cfhf s
Keywords: (3Gdabg GdESdGejs